Use of a learning approach in problem-based teaching. - Sørensen, Ingrid M. (Danish Journal of Nursing / Sygeplejersken, 2011)
A pilot project in nurse training at University College Nordjylland demonstrates that it is possible to support each student's learning approach when providing guided theoretical and clinical instruction and thereby allowing for differentiated teaching facilitating the students' learning, despite the associated challenges facing the students, instructors and nurses in clinical practice.